Assessment of Etiological Factors Reported in the Literature and Their Impact on TMD Incidence in Young Adults - Julia Wójcicka; Szymon Dudziński; Daniil Charnushevich; Wiktoria Musyt (Quality in Sport)
Introduction: Chronic temporomandibular disorders (TMDs) typically result from long-term exposure to factors such as occlusal dysfunction, stress, and parafunctions, and are often associated with older patients. In contrast, young adults, exposed for a shorter time, may recover fully if diagnosed early. However, there is limited data comparing TMD treatment in young adults versus older individuals.